2005
DOI: 10.1364/josab.22.002417
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz time-domain spectroscopy of sulfur-containing biomolecules

Abstract: We present frequency-dependent absorption coefficients and refractive indices of sulfur-containing biomolecules in the far-infrared region measured by terahertz (THz) time-domain spectroscopy (TDS). The THz radiation was generated by a surface photocurrent method with a (100)InAs wafer as a THz emitter, and its intensity was enhanced by applying a magnetic field of 1.6 T. The THz radiation was detected by the electrooptic sampling method with a ZnTe crystal. The characterization of the apparatus of THz TDS is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…The detail of the experimental set up of THz-TDS was already described elsewhere [5,6]. Briefly, femtosecond pulses from a Ti:sapphire oscillator were used for generation and detection of the THz radiation.…”
Section: Methodsmentioning
confidence: 99%
“…The detail of the experimental set up of THz-TDS was already described elsewhere [5,6]. Briefly, femtosecond pulses from a Ti:sapphire oscillator were used for generation and detection of the THz radiation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it becomes possible to achieve the selective detection of certain molecules in mixed samples, which form strong inter-and intramolecular modes in a sample mixed with impurities. Moreover, THz waves cause almost no damage to materials, and so they can be used to detect fragile biological samples [4][5][6][7][8][9] and to characterize pharmaceutical materials. [10][11][12][13] Thus, THz techniques are attracting increasing interest not only in basic research, but also for practical applications in a variety of fields.…”
Section: Introductionmentioning
confidence: 99%
“…The THz-TD absorption spectra of DNA 10 and amino acids [11][12][13][14] have revealed that specific resonance patterns can be identified as the vibrational modes of intermolecular hydrogen bond networks. Recently, we found that incorporating target molecules in nanosized spaces is effective in reducing the influence of the intermolecular modes of the target molecule.…”
Section: Introductionmentioning
confidence: 99%